Special protective slag for forklift fork arm steel and preparation method thereof

CN122999889APending Publication Date: 2026-10-30HENAN XIBAO METALLURGICAL MATERIALS GROUP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611498889.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有常规连铸保护渣主要针对普碳钢、不锈钢等通用钢种设计,未能充分考虑货叉用低合金高强度钢的连铸特性

Benefits of technology

本发明通过上述技术方案提供一种专用于叉车叉臂钢的连铸结晶器保护渣及其制备方法,旨在解决现有技术中叉车叉臂钢连铸过程中因保护渣性能不匹配导致的铸坯表面裂纹、夹渣、漏钢等质量问题。该保护渣能够实现适宜的碱度、黏度和熔化特性,在保证良好润滑性能的同时实现均匀传热,有效减少叉车叉臂钢铸坯表面缺陷,提高成材率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention provides a special protective slag for forklift fork arm steel and its preparation method, belonging to the field of metallurgical auxiliary materials technology. The special protective slag for forklift fork arm steel is composed of the following chemical components by mass percentage: CaO: 28%~35%, SiO2: 26%~32%, Al2O3: 4%~8%, MgO: 3%~6%, Na2O: 6%~10%, F... ‑ The composition of the protective slag is as follows: 3%~6%, Li2O: 1%~3%, total carbon: 6%~12%, with the balance being unavoidable impurities; the basicity R=CaO / SiO2 of the protective slag satisfies: 0.90≤R≤1.20, the viscosity of the protective slag at 1300℃ is 0.6~1.2Pa·s, and the melting temperature is 1100~1180℃. This invention provides a special protective slag for forklift fork arm steel, improving the surface quality of forklift fork arm steel billets, reducing cracks and inclusions, and ensuring smooth continuous casting production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgical auxiliary materials technology, specifically relating to a special protective slag for forklift arm steel and its preparation method. Background Technology

[0002] Forklift forks are key load-bearing components of forklifts, subjected to frequent cyclic loads, impact loads, and bending stresses during operation. Therefore, strict requirements are placed on the fatigue life, hardenability, and mechanical property stability of the steel used. Fork flat steel requires a fatigue life of ≥1 million cycles, narrow hardenability, and stable mechanical properties. Therefore, low-alloy high-strength steel, such as 33MnCrTiB, is typically selected for forklifts.

[0003] Continuous casting flux is a key functional auxiliary material added to the crystallizer during the continuous casting process. It is typically based on silicates and contains various fluxes and carbonaceous framework materials. It melts on the surface of the molten steel to form a three-layer structure: a powdery slag layer, a sintered layer, and a liquid slag layer. It provides insulation, prevents oxidation of the molten steel, adsorbs inclusions, lubricates the cast billet, and improves heat transfer. However, existing conventional continuous casting fluxes are mainly designed for general-purpose steels such as carbon steel and stainless steel, failing to fully consider the continuous casting characteristics of low-alloy high-strength steels used for forks. In actual production, the surface of cast billets of steels such as fork flat bars often exhibits defects such as slag grooves, slag pits, corner cracks, and vibration cracks. These defects are closely related to the mismatch between the physicochemical properties of the flux.

[0004] The main challenges in continuous casting of steel for forks are as follows: First, fork steel has a moderate carbon content and a high content of alloying elements (Cr, Ti, B, etc.). During the solidification process, the peritectic reaction is significant, and the billet shrinkage is large, which can easily lead to uneven solidified billet shells in the crystallizer. If the lubrication performance of the protective slag is insufficient, it can easily lead to sticking and leakage accidents. Second, elements such as Al and Ti in alloy steel can easily react with SiO2 in the protective slag, leading to an increase in the basicity and viscosity of the protective slag, which affects the coordinated control of the heat transfer and lubrication performance of the protective slag. Third, fork flat steel is generally a rectangular billet, and the heat dissipation conditions at the corners are complex. If the heat transfer uniformity of the protective slag is poor, longitudinal and transverse cracks are easily generated at the corners, reducing the yield.

[0005] Therefore, developing a protective slag specifically for continuous casting of forklift fork arm steel and its preparation method to improve the surface quality of the cast billet, reduce cracks and inclusions, and ensure smooth continuous casting production has significant technical value and economic benefits. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a special protective slag for forklift fork arm steel, which improves the surface quality of forklift fork arm steel billets, reduces cracks and slag inclusions, and ensures smooth continuous casting production, in order to address the shortcomings of the prior art.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by this invention is: a special protective slag for forklift fork arm steel, composed of the following chemical components by mass percentage: CaO: 28%~35%, SiO2: 26%~32%, Al2O3: 4%~8%, MgO: 3%~6%, Na2O: 6%~10%, F - The content of the protective slag is 3%~6%, Li2O is 1%~3%, total carbon is 6%~12%, and the balance is unavoidable impurities; the basicity R=CaO / SiO2 of the protective slag satisfies: 0.90≤R≤1.20, the viscosity of the protective slag at 1300℃ is 0.6~1.2Pa·s, and the melting temperature is 1100~1180℃.

[0008] Preferably, the protective slag is composed of the following chemical components by mass percentage: CaO: 30%~33%, SiO2: 28%~31%, Al2O3: 5%~7%, MgO: 4%~5%, Na2O: 7%~9%, F - Li2O: 4%~5%, Li2O: 1.5%~2.5%; Total carbon: 8%~10%.

[0009] Preferably, the basicity R of the protective slag is controlled between 1.00 and 1.10, the viscosity at 1300℃ is 0.8 to 1.0 Pa·s, and the melting temperature is 1130 to 1160℃.

[0010] Preferably, the total carbon is derived from carbonaceous materials, which are compounded from ultra-high carbon black and flake graphite in a mass ratio of 1:2 to 1:4.

[0011] Among them, super carbon black provides rapid carbonization to regulate the melting rate, while flake graphite provides a stable skeleton to control the thickness of the liquid slag layer.

[0012] This invention also provides a method for preparing the above-mentioned protective slag for forklift fork arm steel, comprising the following steps: (1) Weigh the following raw materials: wollastonite, limestone, quartz sand, bauxite, magnesite, soda ash, fluorite, lithium carbonate, super carbon black and flake graphite; (2) Mix the weighed raw materials, mix the powder with water at a mass ratio of 1:0.5 to 1:0.6, stir evenly in a high-speed mixer to make a slurry with uniform concentration; (3) The slurry is transported to the spray granulation tower by a high-pressure pump and atomized by a high-speed centrifugal atomizer. At the same time, hot air is introduced to dry the droplets into hollow spherical particles in the tower. (4) The hollow spherical particles after granulation are screened, and the particles with the target particle size are selected as finished products. After passing the test, they are packaged and stored.

[0013] Preferably, the raw material composition in step (1) is as follows by weight: 23-41 parts wollastonite, 3-22 parts limestone, 9-15 parts quartz sand, 4-9 parts bauxite, 3-6 parts magnesite, 10-15 parts soda ash, 6-11 parts fluorite, 2-7 parts lithium carbonate, 2-3 parts super carbon black and 5-10 parts flake graphite.

[0014] Preferably, the stirring time in step (2) is ≥55 min, and the mass concentration of the slurry is 62-67%.

[0015] Preferably, the inlet temperature of the hot air in step (3) is 580~610℃ and the outlet temperature is 130~160℃.

[0016] Preferably, in step (3), the negative pressure inside the spray granulation tower is controlled at -100~-300Pa to ensure the drying effect and particle sphericity.

[0017] The mechanisms of action of each chemical component in the protective slag of this invention are as follows: CaO and SiO2 are the basic components of the protective slag. CaO, as a basic oxide, increases the basicity of the protective slag, enhancing its ability to absorb inclusions such as Al2O3 in molten steel. SiO2, as an acidic oxide, regulates the viscosity and melting characteristics of the protective slag. This invention controls the CaO / SiO2 basicity between 0.90 and 1.20 (preferably 1.00 to 1.10), ensuring sufficient absorption of inclusions while avoiding the problems of increased viscosity and decreased lubrication performance caused by excessively high basicity. Simultaneously, it prevents the protective slag from precipitating crystals at high temperatures, facilitating the formation of a uniform liquid slag film and achieving uniform heat transfer in the forklift fork arm steel casting.

[0018] The addition of Al2O3 can regulate the viscosity stability of the protective slag. When Al in the molten steel reacts with SiO2 in the protective slag to form Al2O3, appropriate supplementation of Al2O3 can reduce drastic fluctuations in the composition of the protective slag and maintain the stability of its physicochemical properties. Simultaneously, Al2O3 can improve the high-temperature stability of the protective slag and enhance the uniformity of the slag film. This invention controls the Al2O3 content within a suitable range of 4% to 8%, thus achieving its stabilizing effect without causing a significant increase in the melting point of the protective slag due to excessive Al2O3 content.

[0019] The addition of MgO can reduce the viscosity of the protective slag and improve its fluidity. Simultaneously, MgO can reduce the crystallization tendency of the protective slag, which is beneficial for the formation of a glassy slag film, thereby achieving uniform heat transfer and reducing casting defects caused by uneven heat transfer. In this invention, MgO is controlled at 3%~6%.

[0020] As a strong flux, Na₂O can significantly reduce the viscosity and melting temperature of the protective slag, and improve its spreading properties and melting rate. In this invention, the Na₂O content is controlled at 6%~10%, and in conjunction with Li₂O, it can effectively regulate the melting and crystallization behavior of the protective slag.

[0021] Li2O is a highly efficient flux; adding a small amount can significantly reduce the viscosity and melting temperature of the protective slag, and improve its fluidity and lubrication performance in the crystallizer. However, excessive Li2O content can lead to excessively rapid melting of the protective slag and an excessively thin liquid slag layer. Therefore, this invention controls the Li2O content to 1%~3%.

[0022] F - (Derived from fluorite) can reduce the viscosity and melting temperature of the protective slag, improve its fluidity, and facilitate the uniform distribution of liquid slag and lubrication of the cast billet. This invention utilizes F... - The content is controlled at 3% to 6%, which ensures lubrication while reducing the corrosion of the crystallizer copper plate by fluoride and environmental pollution.

[0023] Total carbon (C) plays a skeletal role and regulates the melting rate in protective slag. Carbonaceous materials burn at high temperatures to generate CO2 gas, which forms voids in the slag layer, thus providing insulation and regulating the melting rate. This invention employs a carbonaceous material system composed of super-fine carbon black and flake graphite in a ratio of 1:2 to 1:4. Super-fine carbon black has fine particle size and high reactivity, enabling rapid regulation of the melting rate; flake graphite has coarse particle size and a high degree of graphitization, providing a continuous and stable skeletal function and controlling the thickness of the liquid slag layer. The combination of these two materials allows for the regulation of the melting rate of the protective slag, ensuring the stability of the slag film structure within the crystallizer.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a mold flux specifically for continuous casting of forklift fork arm steel and its preparation method, aiming to solve quality problems such as surface cracks, slag inclusions, and steel leakage in the continuous casting process of forklift fork arm steel caused by mismatched mold flux properties. This mold flux achieves suitable basicity, viscosity, and melting characteristics, ensuring good lubrication while achieving uniform heat transfer, effectively reducing surface defects in forklift fork arm steel billets and improving yield.

[0025] This invention addresses the specific requirements of low-alloy high-strength steel (such as 33MnCrTiB) for forklift arms under rectangular billet continuous casting conditions. It optimizes the chemical composition system of the protective slag, controlling the basicity within a suitable range of 0.90~1.20, the viscosity at 0.6~1.2 Pa·s (1300℃), and the melting temperature at 1100~1180℃. This ensures that the protective slag possesses both a suitable melting rate and good lubrication properties, effectively guaranteeing the thickness and uniform consumption of the liquid slag layer.

[0026] This invention, through the rational control of CaO / SiO2 alkalinity and the content of components such as MgO and Al2O3, ensures that the protective slag maintains stable physicochemical properties even after absorbing Al2O3 inclusions in the molten forklift arm steel, thus avoiding performance degradation caused by compositional changes. Simultaneously, the appropriate alkalinity and viscosity design ensures uniform heat transfer in the slag film, significantly reducing corner cracks and inclusion rates in the forklift arm steel billet.

[0027] This invention employs a carbonaceous material system composed of super-carbon black and flake graphite, achieving precise control over the melting rate of the protective slag and the thickness of the liquid slag layer. Super-carbon black reacts rapidly to regulate the initial melting rate, preventing the protective slag from forming a crust on the surface of the molten steel; flake graphite provides a stable and durable skeletal support, controlling the thickness of the liquid slag layer within a reasonable range. The synergistic effect of the two enables the protective slag to form a stable three-layer structure of powder slag layer-sintered layer-liquid slag layer in the crystallizer, ensuring both heat insulation and continuous and uniform lubrication for the cast billet.

[0028] The preparation method of this invention employs a spray granulation process, resulting in a protective slag that is composed of hollow spherical particles with a low bulk density (0.6~0.8 g / cm³). 3 It has good spreadability and can quickly and evenly spread on the surface of the molten steel in the crystallizer to form a covering layer, effectively preventing secondary oxidation of the molten steel, while improving the heat preservation performance of the protective slag.

[0029] Using the protective slag of this invention for continuous casting of forklift arm steel results in no slag grooves or pits on the surface of the billet, reduces the crack incidence rate by more than 60%, increases the qualified rate of continuous casting billets by more than 3%, and eliminates sticking and leakage accidents during continuous casting. It enables continuous casting in multiple heats, and has good economic benefits and promising prospects for promotion and application. Detailed Implementation

[0030] To better understand the present invention, the following embodiments further illustrate the content of the invention, but the scope of protection of the present invention is not limited to the following embodiments. Numerous specific details are set forth in the following description to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the present invention can be practiced without one or more of these details.

[0031] Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention.

[0032] To make the objectives and advantages of this invention clearer, the following detailed description, in conjunction with specific embodiments, illustrates the special protective slag for forklift fork arm steel, its preparation method, and its effects. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Unless otherwise specified, the following embodiments do not include components other than unavoidable impurities. Unless otherwise specified, the raw materials and instruments used in the embodiments are conventionally selected in the art. Experimental methods not specifying specific conditions in the embodiments were implemented under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.

[0033] Example 1: Special protective slag for forklift fork arm steel, composed of the following chemical components by mass percentage: CaO: 31.5%, SiO2: 30.0%, Al2O3: 5.5%, MgO: 4.5%, Na2O: 7.5%, F - 4.5% Li2O, 2.0% C (total carbon), balance being impurities; basicity R=1.05, viscosity at 1300℃ is 0.9 Pa·s, melting temperature is 1145℃.

[0034] The preparation method of this special protective slag for forklift fork arm steel is carried out according to the following steps: (1) Weigh the following raw materials in parts by weight: 35 parts wollastonite, 10 parts limestone, 9 parts quartz sand, 6 parts bauxite, 5 parts magnesite, 12 parts soda ash, 9 parts fluorite, 5 parts lithium carbonate, 2 parts super carbon black and 7 parts flake graphite. (2) Mix the weighed raw materials, mix the powder with water at a mass ratio of 1:0.5, and stir in a high-speed mixer for 60 minutes to make a uniform slurry with a concentration of 66.7%; (3) The slurry is transported to the spray granulation tower by a high-pressure pump. The negative pressure inside the tower is controlled at -200Pa. The slurry is atomized by a high-speed centrifugal atomizer. At the same time, the inlet temperature of the hot air furnace is 590°C and the outlet temperature is 145°C, so that the droplets are dried into hollow spherical particles inside the tower. (4) The hollow spherical granules after granulation are screened by a vibrating screen, and granules with a particle size of 0.15~1.0mm are selected as finished products. After passing the inspection, they are bagged and packaged.

[0035] Example 2: Special protective slag for forklift fork arm steel, composed of the following chemical components by mass percentage: CaO: 32.0%, SiO2: 29.5%, Al2O3: 6.0%, MgO: 4.0%, Na2O: 8.0%, F - 4.0%, Li2O: 2.5%, C (total carbon): 9.0%, balance is impurities; basicity R=1.08, viscosity at 1300℃ is 0.85Pa·s, melting temperature is 1150℃.

[0036] The preparation method of this special protective slag for forklift fork arm steel is carried out according to the following steps: (1) Weigh the following raw materials in parts by weight: 30 parts wollastonite, 17 parts limestone, 9 parts quartz sand, 6 parts bauxite, 4 parts magnesite, 12 parts soda ash, 8 parts fluorite, 5 parts lithium carbonate, 2 parts super carbon black and 7 parts flake graphite. (2) Mix the weighed raw materials, mix the powder with water at a mass ratio of 1:0.6, and stir in a high-speed mixer for 58 minutes to make a uniform slurry with a concentration of 62.5%; (3) The slurry is transported to the spray granulation tower by a high-pressure pump. The negative pressure inside the tower is controlled at -100Pa. The slurry is atomized by a high-speed centrifugal atomizer. At the same time, the inlet temperature of the hot air furnace is 580°C and the outlet temperature is 130°C, so that the droplets are dried into hollow spherical particles inside the tower. (4) The hollow spherical granules after granulation are screened by a vibrating screen, and granules with a particle size of 0.15~1.0mm are selected as finished products. After passing the inspection, they are bagged and packaged.

[0037] Example 3: Special protective slag for forklift fork arm steel, composed of the following chemical components by mass percentage: CaO: 30.5%, SiO2: 30.5%, Al2O3: 6.5%, MgO: 5.0%, Na2O: 7.0%, F - 5.0%, Li2O: 1.5%, C (total carbon): 8.0%, balance is impurities; basicity R=1.00, viscosity at 1300℃ is 1.0 Pa·s, melting temperature is 1135℃.

[0038] The preparation method of this special protective slag for forklift fork arm steel is carried out according to the following steps: (1) Weigh the following raw materials in parts by weight: 41 parts wollastonite, 3 parts limestone, 9 parts quartz sand, 8 parts bauxite, 5 parts magnesite, 11 parts soda ash, 11 parts fluorite, 4 parts lithium carbonate, 2 parts super carbon black and 6 parts flake graphite. (2) Mix the weighed raw materials, mix the powder with water at a mass ratio of 1:0.55, and stir in a high-speed mixer for 60 minutes to make a uniform slurry with a concentration of 64.5%; (3) The slurry is transported to the spray granulation tower by a high-pressure pump. The negative pressure inside the tower is controlled at -300Pa. The slurry is atomized by a high-speed centrifugal atomizer. At the same time, the inlet temperature of the hot air furnace is 610°C and the outlet temperature is 160°C, so that the droplets are dried into hollow spherical particles inside the tower. (4) The hollow spherical granules after granulation are screened by a vibrating screen, and granules with a particle size of 0.15~1.0mm are selected as finished products. After passing the inspection, they are bagged and packaged.

[0039] The chemical composition of the special protective slag for forklift fork arm steel in Examples 4-10 is shown in Table 1, the performance indicators are shown in Table 2, the raw material composition is shown in Table 3, and the preparation method is the same as in Example 1.

[0040] Table 1. Chemical composition (wt%) of the special protective slag for forklift arm steel in Examples 4-10

[0041] Table 2 Performance Indicators of Special Protective Slag for Forklift Arm Steel in Examples 4-10

[0042] Table 3. Raw material composition (parts by weight) of special protective slag for forklift fork arm steel in Examples 4-10.

[0043] The following are comparative examples. The chemical composition of the protective slag in Comparative Examples 1-5 is shown in Table 4, the performance indicators of the protective slag in Comparative Examples 1-5 are shown in Table 5, the raw material composition is shown in Table 6, and the preparation method is the same as in Example 1.

[0044] Table 4 Chemical composition (wt%) of protective slag in Comparative Examples 1-5

[0045] Table 5 Performance indicators of protective slag in Comparative Examples 1-5

[0046] Table 6. Raw material composition (parts by weight) of protective slag in Comparative Examples 1-5

[0047] To verify the technical effect of the present invention, the protective slags prepared in Examples 1-3 and Comparative Examples 1-6 were applied to the continuous casting production of forklift fork arm steel. The continuous casting cross-section was a rectangular billet with a size of 230×280mm, the casting speed was 0.9-1.2m / min, and the steel grade was 33MnCrTiB (forklift-specific steel). The surface quality of the billet, the presence of exposed steel, and the billet qualification rate were observed and statistically analyzed.

[0048] Crack rate: After continuous casting, the surface of each batch of billets is visually inspected and supplemented with pickling and flaw detection; the number of billets with corner cracks, surface longitudinal cracks or transverse cracks is counted. Crack rate = number of billets with cracks / total number of billets × 100%.

[0049] Slag inclusion rate: Visual inspection of the surface of the billet is carried out, and subcutaneous slag inclusions are detected by ultrasonic testing; the number of billets with slag inclusion defects is counted, and the slag inclusion rate = number of billets with slag inclusions / total number of billets × 100%.

[0050] Number of steel leakage incidents: During the continuous casting process, the number of steel leakage incidents caused by adhesion, slag entrapment or poor lubrication is recorded, and is counted as incidents per casting.

[0051] Qualification rate: After surface cleaning and inspection, the number of qualified billets that meet the requirements for subsequent rolling is counted. Qualification rate = number of qualified billets / total number of billets × 100%.

[0052] The experimental results are shown in Table 7.

[0053] Table 7 Statistical Table of Experimental Results

[0054] Experimental results show that using the protective slag from Examples 1-3 of this invention for continuous casting of forklift fork arm steel significantly reduces the surface crack rate and slag inclusion rate of the cast billet, increases the continuous casting qualification rate by more than 3%, and prevents steel leakage accidents during the entire casting process, ensuring smooth continuous casting operation. The fork flat steel billets cast using the protective slag of this invention have smooth surfaces, uniform and clear vibration marks, no slag grooves or pits, and no transverse or longitudinal cracks at the corners. The billets can be directly rolled after surface cleaning.

[0055] Comparative Example 1 had a basicity of 1.30, a crack rate of 2.5%, an inclusion rate of 1.8%, and two instances of steel leakage, with a pass rate of 95.2%. This indicates that when the basicity of the protective slag exceeds 1.20, the heat transfer uniformity of the slag film deteriorates, lubrication is insufficient, and longitudinal cracks are generated. In severe cases, this can lead to sticking and steel leakage, failing to meet the requirements of coordinated control of lubrication and heat transfer in continuous casting of forklift fork arm steel.

[0056] Comparative Example 2 had a basicity of 0.80, a crack rate of 1.1%, an inclusion rate of 1.6%, and one steel leakage, with a pass rate of 96.0%. This indicates that when the basicity of the protective slag is below 0.90, the protective slag's ability to absorb Al2O3 inclusions in the molten steel is insufficient, leading to an increase in surface longitudinal cracks and inclusion defects. Poor lubrication also increases the risk of steel leakage, making it impossible to simultaneously meet the dual requirements of inclusion absorption and stable lubrication.

[0057] Comparative Example 3 had a viscosity of 1.5 Pa·s, a crack rate of 1.8%, an inclusion rate of 0.9%, and two instances of steel leakage, with a pass rate of 95.8%. This indicates that when the viscosity of the protective slag exceeds 1.2 Pa·s, the continuity of the lubricating film is poor, the oscillation marks on the billet become disordered, and steel leakage occurs due to adhesion, resulting in a sharp decrease in the lubrication capacity for the forklift fork arm steel.

[0058] Comparative Example 4 had a melting temperature of 1210℃, a crack rate of 1.9%, an inclusion rate of 0.9%, one instance of steel leakage, and a pass rate of 95.5%. Poor lubrication of the protective slag led to deep vibration marks on the surface of the billet and an increase in transverse cracks at the corners. Poor lubrication caused steel leakage, indicating that when the melting temperature of the protective slag exceeds 1180℃, it cannot provide sufficient liquid slag lubrication for the forklift fork arm steel.

[0059] In Comparative Example 5, the carbonaceous material was entirely provided by flake graphite, with a crack rate of 1.5%, an inclusion rate of 1.0%, one instance of steel leakage, and a pass rate of 96.8%. When flake graphite was used alone, the initial melting rate of the protective slag was too slow, and the thickness of the liquid slag layer was unstable. At the same time, the flake graphite skeleton effect was too strong, resulting in slag surface crusting, untimely liquid slag replenishment, and a decrease in lubrication and heat preservation effects. The number of cracks and inclusion defects on the surface of the billet increased. This indicates that the combination of super carbon black and flake graphite enables the controllable adjustment of the melting rate of the protective slag in this invention, which is particularly important for continuous casting of forklift fork arm steel.

[0060] The above experimental results demonstrate that the protective slag of this invention achieves controllable adaptation to the continuous casting process of forklift arm steel through the synergistic effect of three core performance indicators: basicity R=0.90~1.20, viscosity at 1300℃ 0.6~1.2Pa·s, and melting temperature 1100~1180℃. The protective slag of this invention possesses both excellent lubrication properties and uniform heat transfer capabilities, thereby controlling the corner crack rate of forklift arm steel billets to below 1.0%, the inclusion rate to below 0.8%, eliminating steel leakage accidents, and increasing the billet qualification rate to over 98%.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention, as long as they do not depart from the spirit and scope of the technical solutions of the present invention, should be covered within the scope of the claims of the present invention.

Claims

1. A special protective slag for forklift fork arm steel, characterized in that: Composed of the following chemical components by mass percentage: CaO: 28%~35%, SiO2: 26%~32%, Al2O3: 4%~8%, MgO: 3%~6%, Na2O: 6%~10%, F - The content of the protective slag is 3%~6%, Li2O is 1%~3%, total carbon is 6%~12%, and the balance is unavoidable impurities; the basicity R=CaO / SiO2 of the protective slag satisfies: 0.90≤R≤1.20, the viscosity of the protective slag at 1300℃ is 0.6~1.2Pa·s, and the melting temperature is 1100~1180℃.

2. The protective slag for forklift fork arm steel as described in claim 1, characterized in that: Composed of the following chemical components by mass percentage: CaO: 30%~33%, SiO2: 28%~31%, Al2O3: 5%~7%, MgO: 4%~5%, Na2O: 7%~9%, F - Li2O: 4%~5%, Li2O: 1.5%~2.5%; Total carbon: 8%~10%, the balance being unavoidable impurities.

3. The protective slag for forklift fork arm steel as described in claim 1, characterized in that: The alkalinity R is controlled between 1.00 and 1.10, the viscosity at 1300℃ is 0.8 to 1.0 Pa·s, and the melting temperature is 1130 to 1160℃.

4. The protective slag for forklift fork arm steel as described in claim 1, characterized in that: The total carbon is derived from carbonaceous materials, which are composed of super carbon black and flake graphite in a mass ratio of 1:2 to 1:

4.

5. The method for preparing special protective slag for forklift fork arm steel as described in any one of claims 1-4, characterized in that: Includes the following steps: (1) Weigh the following raw materials: wollastonite, limestone, quartz sand, bauxite, magnesite, soda ash, fluorite, lithium carbonate, super carbon black and flake graphite; (2) Mix the weighed raw materials, mix the powder with water at a mass ratio of 1:0.5 to 1:0.6, stir evenly in a high-speed mixer to make a slurry with uniform concentration; (3) The slurry is transported to the spray granulation tower by a high-pressure pump and atomized by a high-speed centrifugal atomizer. At the same time, hot air is introduced to dry the droplets into hollow spherical particles in the tower. (4) The hollow spherical particles after granulation are screened, and the particles with the target particle size are selected as finished products. After passing the test, they are packaged and stored.

6. The method for preparing the special protective slag for forklift fork arm steel as described in claim 5, characterized in that: The raw material composition in step (1) is as follows by weight: 23-41 parts wollastonite, 3-22 parts limestone, 9-15 parts quartz sand, 4-8 parts bauxite, 3-6 parts magnesite, 10-15 parts soda ash, 6-11 parts fluorite, 2-7 parts lithium carbonate, 2-3 parts super carbon black and 5-10 parts flake graphite.

7. The method for preparing the special protective slag for forklift fork arm steel as described in claim 5, characterized in that: The stirring time in step (2) is ≥55 min, and the mass concentration of the slurry is 62-67%.

8. The method for preparing the special protective slag for forklift fork arm steel as described in claim 5, characterized in that: The inlet temperature of the hot air in step (3) is 580~610℃, and the outlet temperature is 130~160℃.

9. The method for preparing the special protective slag for forklift fork arm steel as described in claim 5, characterized in that: In step (3), the negative pressure inside the spray granulation tower is controlled at -100~-300Pa.